PROTAGONISMO NEGRO NA EDUCAÇÃO: CONFLUÊNCIAS DE MARIA DE JESUS E CONCEIÇÃO EVARISTO - Santos Pinheiro, Erlan; Rangel Filho, Marcelo Eustáquio; Gabriel Dantas, Maycon; Ferreira Lopes, Lúcia Helena; Rodrigues Teixeira e Silva, Letícia (Intercursos, 2025)
não consta